ANALISIS KUALITAS INSTRUMEN PENILAIAN YANG DIGUNAKAN GURU DI SEKOLAH - Feby Ayu Maharani; Najwa Berka Amanda; Shafa Zakiyah; Jelita Irmananda; Perkasa Dinanti Akbar; Riska Listiani Putri; Handoko (STKIP Subang, 2026)
This study aimed to analyze the quality of assessment instruments used by teachers in schools during the learning evaluation process. The research employed a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation studies. The research subjects consisted of elementary school teachers directly involved in developing and implementing assessment instruments. The analysis focused on aspects of validity, reliability, alignment with learning objectives, item difficulty level, use of assessment rubrics, and challenges encountered by teachers in developing evaluation instruments. The findings revealed that teachers had made efforts to design assessment instruments based on predetermined learning objectives and indicators. The instruments used were diverse, including written tests, observations, projects, and performance assessments. However, several challenges were still identified, such as limited time, assessment subjectivity, and difficulties in determining cognitive levels appropriate to students’ abilities. In addition, teachers still required more comprehensive training in developing valid and reliable assessment instruments. This study is expected to serve as an evaluation reference for teachers and schools in improving the quality of assessment instruments to measure students’ learning outcomes more objectively, accurately, and in accordance with curriculum demands.